Age characteristics of first formers' readiness to musical upbringing at Primary school - Lyubar, R.O. (Pedagogy of Higher and Secondary Education, 2006)
The issues of age peculiarities of the development of six year old children are brought up in the article. The physical м mental peculiarities are analyzed, the leaching techniques for singing of six year old students at Music lessons at Primary school.